119k views
4 votes
Which shows the correct substitution of the values a, b, and c from the equation 0 = 4x2 + 2x – 1 into the quadratic formula below?

Quadratic formula: x =

User Magma
by
4.6k points

2 Answers

2 votes

For this case we have a quadratic equation given by:


4x ^ 2 + 2x-1 = 0

The roots are found by means of the quadratic formula below:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}

Where:


a = 4\\b = 2\\c = -1

So, we have:


x = \frac {-2 \pm \sqrt {2 ^ 2-4 (4) (- 1)}} {2 (4)}

Or in an equivalent way we have:


x = \frac {-2 \pm \sqrt {2 ^ 2 + 4 (4) (1)}} {2 (4)}

Answer:

The correct option will be:


x = \frac {-2 \pm \sqrt {2 ^ 2-4 (4) (- 1)}} {2 (4)}

User Sanju Menon
by
5.0k points
3 votes

Answer:

a = 4, b = 2 and c= -1

Explanation:

Quadratic formula: x =√[-b ± v(b² - 4ac)]/2a

Here quadratic equation is 4x2 + 2x – 1

a = 4, b = 2 and c= -1

x =[-b ± √(b² - 4ac)]/2a

= [-2 ± √(2² - 4*4*-1)]/2*4

= [-2 ± √(4 + 16)]/8

= [-2 ± √20)]/8

= [-2 ± 2√5)]/8

= [-1 ± √5)]/4

x = [-1 ± √5)]/4

User Miguel Peniche
by
4.9k points